Portrayal of Valour of Woman Protagonist in Rabindranath Tagore’s Giribala (International Journal of Food and Nutritional Sciences, 2022)
Rabindranath Tagore has contributed immensely in the development of Indian literature as a writer. His works are an emblem of salient features of Indian patriarchal society. He has also depicted status of women in Indian society in the context of male domination leading to sufferings and exploitation of women in 19th century. Giribala is one of the finest stories dealing with an ordinary woman demonstrating an extra- ordinary courage in order to protect her dignity and identity. The protagonist has challenged the traditional stereotypes of woman as a care taker, wife, slave, commodity and mother. As an innovative educator, Tagore often urges women to searchfor freedom, decision making power and establish their own rightful identity in the fabric of the society. There is self-awakening of feminine potentiality and desire for economic independence by the protagonist in the development of the story.This resea